2004
DOI: 10.1101/gad.1232504
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and cancer

Abstract: Epigenetic mechanisms act to change the accessibility of chromatin to transcriptional regulation locally and globally via modifications of the DNA and by modification or rearrangement of nucleosomes. Epigenetic gene regulation collaborates with genetic alterations in cancer development. This is evident from every aspect of tumor biology including cell growth and differentiation, cell cycle control, DNA repair, angiogenesis, migration, and evasion of host immunosurveillance. In contrast to genetic cancer causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
325
0
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(339 citation statements)
references
References 265 publications
(249 reference statements)
2
325
0
12
Order By: Relevance
“…DNA hypermethylation in promoter regions is associated with silencing of tumor suppressor genes because of direct or indirect prevention to accessing transcription factors in the promoter region. 22 Recent studies 21,23,24 have demonstrated that CpG island hypermethylation, via silencing of key cancer-related genes, plays a major causal role in cancer, including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…DNA hypermethylation in promoter regions is associated with silencing of tumor suppressor genes because of direct or indirect prevention to accessing transcription factors in the promoter region. 22 Recent studies 21,23,24 have demonstrated that CpG island hypermethylation, via silencing of key cancer-related genes, plays a major causal role in cancer, including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation homeostasis is a major epigenetic mechanism in cancer development and heart dysfunction [18][19][20], which is tightly regulated by the opposing histone acetyltransferases (HATs) and histone deacetylases (HDACs) [21,22]. Acetylation of histones opens chromatin structure for gene transcription; and acetylation also stabilizes and activates transcription factors for an increased activation of target genes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Within the last few years, a number of reviews with an emphasis on various aspects of epigenetic modifications in cancer have been published [11][12][13][14][15]. In this review, we will focus on hypermethylation and tumor suppressor gene silencing in cancer development, particularly in virus-associated cancers.…”
Section: Introductionmentioning
confidence: 99%